Pengaruh Employee Engagement Dan Commitment Organization Terhadap Kinerja Pegawai Melalui Kepuasan Kerja Pegawai Sebagai Variabel Intervening (Studi pada Departemen Operasi PT Cogindo DayaBersama PLTU Pelabuhan Ratu) - Chaerunissa, Elida; Pancasasti, Ranthy (Jurnal Riset Bisnis dan Manajemen Tirtayasa, 2021)
This study aims to analyze (1) the magnitude of the effect of employee engagement on employee performance, (2) the magnitude of the influence of employee engagement on employee job satisfaction, (3) the magnitude of the influence of organizational commitment on employee job satisfaction, (4) the magnitude of the influence of organizational commitment on employee performance. , and (5) the magnitude of the effect of job satisfaction on the performance of employees of PT Cogindo DayaBersama. The population in this study were employees of PT Cogindo Daya Bersama PLTU Pelabuhan Ratu Unit Operations Department with a population of 125 employees and a sample of 100 employees. The results show that employee engagement has a positive and significant effect on employee performance by 76.6 percent and job satisfaction has a positive and significant effect on employee performance by 65.5 percent. This direct effect shows that employee engagement has a positive and significant effect on employee performance, employee engagement has a positive and significant effect on job satisfaction, organizational commitment has a positive and significant effect on job satisfaction, organizational commitment has no effect on employee performance and job satisfaction has a positive and significant effect on job satisfaction. employee performance